Citizens of Delhi lead resilience action. Issue 1 (4th February 2019) - Gupta, Manu; Talankar, Parag; Chavda, Shivangi
Abstract : Purpose: The purpose of this paper is to illustrate practical approaches to addressing issues of risk reduction and disaster prevention in urban areas. In addition to exposure to natural hazards, urban areas represent complex risks and vulnerabilities together with complicated governance structures. Design/methodology/approach: To address the challenge, SEEDS mobilised a "Disaster Watch Forum" – a citizens' platform that brought citizens together to proactively engage with the local government. With hand-holding support from SEEDS, training by domain experts, internal team building and the forum has become a credible people-based institution addressing issues of risk reduction and prevention. Findings: Urban risk reduction has remained a challenging issue with solutions often sought in high investment structural interventions. These have limited impact on the urban poor living in informal areas. This paper reveals "bottom-up" people-based approach that is able to engage with the "system" from "outside". It reveals how people relate to day-to-day risks that affect their lives, making it the stepping stone to address higher order societal risks. Finally, the immense power and energy of youth and children work as local "agents of change". Overall, the work aligns with priorities of the Sendai Framework for Disaster Risk Reduction. Research limitations/implications: There are three principal implications for further research: with half the world now urbanized, urgent solutions are needed for improving disaster risk governance in cities; taking a "whole of society" approach in addressing a wider canvas of risks; and redirecting investments in urban areas towards managing risks, rather than managing disasters. Practical implications: The model illustrated is replicable in urban areas facing risk. It worked well in a population catchment of 50, 000 residents; to achieve scale would require enabling a federated structure of several localised forums. Originality/value: The paper presents a hands-on experience in building an alternative approach to urban risk reduction. It has required authors to move from "government to governance" model making citizens active stakeholders in proactively addressing their own underlying vulnerabilities that lead to creation of and exacerbation of risks.